Porcine neonatal blood dendritic cells, but not monocytes, are more responsive to TLRs stimulation than their adult counterparts. - Gael Auray; Marina R Facci; Jill van Kessel; Rachelle Buchanan; Lorne A Babiuk; Volker Gerdts (PLoS ONE, 2013)
The neonatal immune system is often considered as immature or impaired compared to the adult immune system. This higher susceptibility to infections is partly due to the skewing of the neonatal immune response towards a Th2 response. Activation and maturation of dendritic cells (DCs) play an important role in shaping the immune response, therefore, DCs are a target of choice for the development of efficient and protective vaccine formulations able to redirect the neonatal immune response to a protective Th1 response. As pigs are becoming more important for vaccine development studies due to their similarity to the human immune system, we decided to compare the activation and maturation of a subpopulation of porcine DCs in adult and neonatal pigs following stimulation with different TLR ligands, which are promising candidates for adjuvants in vaccine formulations. Porcine blood derived DCs (BDCs) were directly isolated from blood and consisted of a mix of conventional and plasmacytoid DCs. Following CpG ODN (TLR9 ligand) and imiquimod (TLR7 ligand) stimulation, neonatal BDCs showed higher levels of expression of costimulatory molecules and similar (CpG ODN) or higher (imiquimod) levels of IL-12 compared to adult BDCs. Another interesting feature was that only neonatal BDCs produced IFN-α after TLR7 or TLR9 ligand stimulation. Stimulation with CpG ODN and imiquimod also induced enhanced expression of several chemokines. Moreover, in a mixed leukocyte reaction assay, neonatal BDCs displayed a greater ability to induce lymphoproliferation. These findings suggest that when stimulated via TLR7 or TLR9 porcine DCs display similar if not better response than adult porcine DCs.